A novel gravity sedimentation - Forward osmosis hybrid technology for microalgal dewatering. (December 2022) - Ma, Cong; Wang, Guanying; Liu, Xinying; Li, Yajing; Huang, Jingyun; Zhang, Pengda; Chu, Xiuru; Wang, Liang; Zhao, Bin; Zhang, Zhaohui
Abstract: A novel gravity sedimentation - forward osmosis (G-FO) hybrid reactor was built up for separating and concentrating the biomass from the algal-rich water (microalgal dewatering). The extracellular organic matter (EOM) from Chlorella vulgaris ( C. vulgaris ) was divided into dissolved EOM (dEOM) and bound EOM (bEOM). Water flux, flux recovery rate and moisture content (MC) were investigated. Through sedimentation rate, zeta potential and hydrophilicity/hydrophobicity to analyze the experimental results. Scanning electronic microscopy (SEM) was used to observe the different morphologies of accumulated algae cells and EOM on the surface of the membrane. The results showed that cell + bEOM solution had the fastest sedimentation rate and fewest negative charge, so the pollutants accumulated more easily on the membrane surface, resulting in the highest flux decline. Its algal cake layer was the densest from the view of SEM. Cell + bEOM + dEOM solution had the lowest flux decline and the cake layer was the loosest. Cell + bEOM solution had the most severe irreversible fouling and the lowest flux recovery rate (FRR). The membrane fouling of cell solution was lower than that of cell + bEOM + dEOM solution, and the FRR of cell solution was almost 100%. According to the nonionic macro-porous resin fraction results of EOM, cell + bEOM + dEOM solution contained more hydrophilic components, resulting in the lowest MC. On the contrary, cell + bEOM solution showed the highest MC, which contained more hydrophobic components. Effects of bEOM and dEOM on microalgae dewatering performance of a novel gravity sedimentation - forward osmosis (G-FO) hybrid system were investigated, which provided a theoretical basis for large-scale application of FO technology for microalgae dewatering. Highlights: A novel G-FO hybrid system is constructed for microalgae dewatering. The loosest algal cake layer formed by dissolved EOM maintains high water flux. Flux recovery rate mainly relates to the characteristics of EOM. The low moisture content because of the hydrophilic organics of EOM.